2022
DOI: 10.1111/febs.16555
|View full text |Cite
|
Sign up to set email alerts
|

SERF, a family of tiny highly conserved, highly charged proteins with enigmatic functions

Abstract: Amyloid formation is a misfolding process that has been linked to age‐related diseases, including Alzheimer's and Huntington's. Understanding how cellular factors affect this process in vivo is vital in realizing the dream of controlling this insidious process that robs so many people of their humanity. SERF (small EDRK‐rich factor) was initially isolated as a factor that accelerated polyglutamine amyloid formation in a C. elegans model. SERF knockouts inhibit amyloid formation of a number of proteins that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 103 publications
2
32
0
Order By: Relevance
“…As an emerging cellular component, [9][10][11][12][13] rG4 quadruplexes may function as translational repressors and transcriptional regulators, as well as being involved with mRNA processing, mRNA polyadenylation and splicing, telomere maintenance, and RNA translocation, 3,10,14,16,47,[71][72][73][74] although their mechanism of action remains unclear. 36,75 In findings likely relevant to ours, it had recently been found that stress enhances the amount of rG4 quadruplexes present, 4 rG4 quadruplexes are abundant in stress granules, stress promotes rG4 quadruplex folding 4 and RNA quadruplexes may facilitate the formation of stress granules. 5,76 A handful of RNA binding proteins, such as FMRP, nucleolin, CNBP, eIF4A, hnRNPA1, and DHX36, have been shown to bind rG4 quadruplexes, and modulate their folding.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…As an emerging cellular component, [9][10][11][12][13] rG4 quadruplexes may function as translational repressors and transcriptional regulators, as well as being involved with mRNA processing, mRNA polyadenylation and splicing, telomere maintenance, and RNA translocation, 3,10,14,16,47,[71][72][73][74] although their mechanism of action remains unclear. 36,75 In findings likely relevant to ours, it had recently been found that stress enhances the amount of rG4 quadruplexes present, 4 rG4 quadruplexes are abundant in stress granules, stress promotes rG4 quadruplex folding 4 and RNA quadruplexes may facilitate the formation of stress granules. 5,76 A handful of RNA binding proteins, such as FMRP, nucleolin, CNBP, eIF4A, hnRNPA1, and DHX36, have been shown to bind rG4 quadruplexes, and modulate their folding.…”
Section: Discussionsupporting
confidence: 66%
“…SERF proteins were initially identified as a driver of amyloid formation, a process that has been linked to a number of age related diseases, 3336 but their normal physiological functions remain obscure. 36 SERF proteins are remarkably small, averaging about ∼70 amino acids in length, and they share a conserved, highly charged N-terminal domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A π‐π stacked interaction was also established between the unsaturated ring B and the amino acid Tyr62 at the distance of 4.12 Å. This compound showed a similar binding pattern as observed for reference inhibitor acarbose such as Val 163 and most importantly the polar interaction with the catalytic amino acid Asp 300 [34,35] …”
Section: Resultssupporting
confidence: 57%
“…This compound showed a similar binding pattern as observed for reference inhibitor acarbose such as Val 163 and most importantly the polar interaction with the catalytic amino acid Asp 300. [34,35] In the compound 4/α-glucosidase complex (Figure 6 C and D), many intermolecular interactions are established between the docked molecule and the active amino acids of α-glucosidase including conventional hydrogen bonds, carbon hydrogen bonds, π-π T-shaped and π-π stacked interactions. Five hydrogen bonds are formed in the C4/α-glucosidase complex.…”
Section: Molecular Docking Studymentioning
confidence: 99%